Cytokinin increases vegetative growth period by suppressing florigen expression in rice and maize - Cho, Lae-Hyeon; Yoon, Jinmi; Tun, Win; Baek, Gibeom; Peng, Xin; Hong, Woo-Jong; Mori, Izumi C.; Hojo, Yuko; Matsuura, Takakazu; Kim, Sung-Ryul; Kim, Sun-Tae; Kwon, Soon-Wook; et al. (Wiley, 2022)
Increasing the vegetative growth period of crops can increase biomass and grain yield. In rice (Oryza sativa), the concentration of trans ‐zeatin, an active cytokinin, was high in the leaves during vegetative growth and decreased rapidly upon induction of florigen expression, suggesting that this hormone is involved in the regulation of the vegetative phase. To elucidate whether exogenous cytokinin application influences the length of the vegetative phase, we applied 6‐benzylaminopurine (BAP) to rice plants at various developmental stages. Our treatment delayed flowering time by 8–9 days when compared with mock‐treated rice plants, but only at the transition stage when the flowering signals were produced. Our observations also showed that flowering in the paddy field is delayed by thidiazuron, a stable chemical that mimics the effects of cytokinin. The transcript levels of florigen genes Heading date 3a (Hd3a) and Rice Flowering locus T1 (RFT1) were significantly reduced by the treatment, but the expression of Early heading date 1 (Ehd1), a gene found directly upstream of the florigen genes, was not altered. In maize (Zea mays), similarly, BAP treatment increased the vegetative phage by inhibiting the expression of ZCN8, an ortholog of Hd3a. We showed that cytokinin treatment induced the expression of two type‐A response regulators (OsRR1 and OsRR2) which interacted with Ehd1, a type‐B response regulator. We also observed that cytokinin did not affect flowering time in ehd1 knockout mutants. Our study indicates that cytokinin application increases the duration of the vegetative phase by delaying the expression of florigen genes in rice and maize by inhibiting Ehd1.